Intercultural challenge to language learning - Muñoz de Cote, Luz María; van Dijk, Sylvia (Studies in Second Language Learning and Teaching, 2012)
This paper presents the findings of a qualitative research project set to investigate the piloting process of an innovative language program for university students. It challenges traditional English language teaching courses celebrating a view centered on learning; classes become spaces for students to understand the language they are learning through the development of small projects. The approach moves from a teaching transmission paradigm to one where the most important agent is each student who has to engage with a topic of his or her interest. Students are seen as individuals whose knowledge and understanding of the world is valued and not as people whose lack of language skills prevents them from engaging in discussions of complex topics. The objective of this innovation is to enhance students’ understanding and use of academic English in their field of interest. In this project, we argue that knowledge and understanding of the mother tongue and culture play key roles in the development of a second language. A number of studies suggest that students who had strong first language literacy skills achieved higher proficiency levels in their second language. Based on this argument and Vygotsky’s sociocultural learning theory, we designed disciplinary content language learning workshops for first-degree students. The main tenet is that students can develop academic English given that they know about their discipline. Findings so far reveal the difficulty of students to take distance from their previous learning experiences. They also show that students’ ideas expressed in English are far more complex than what would be expected of them given their second language skills. The complexity is not only related to thecontent, but to the way they construct their paragraphs and the understanding of how the register of their field may be used.